2013
DOI: 10.4028/www.scientific.net/amm.469.336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paper on Color Reproduction Quality in Ink-Jet Printing

Abstract: In digital printing process, the color reproduction quality is no longer determined by printing sequence, trapping, solid density and etc., since the technique is different from traditional printing technology. In order to analyze the effects of paper on color reproduction quality in digital ink-jet printing, three kinds of commercial paper were selected and a set of experiments were carried out by using color management technique to simulate the digital proofing. The density and chromaticity of both primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…25 Here, R i is the output of the pattern layer, X is the input variable and X i is the learning sample corresponding to the neuron i. The summation layer has two neurons, as shown in Equation (6), where S D is the arithmetic sum of the outputs of each neuron in the pattern layer and S N is the weighted sum of the value of each neuron in the pattern layer multiplied by the target value y i . The last layer of the network is the linear output layer, which uses the linear function as the transfer function, as shown in Equation ( 7)…”
Section: Neural Network Aided Original Adjustment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Here, R i is the output of the pattern layer, X is the input variable and X i is the learning sample corresponding to the neuron i. The summation layer has two neurons, as shown in Equation (6), where S D is the arithmetic sum of the outputs of each neuron in the pattern layer and S N is the weighted sum of the value of each neuron in the pattern layer multiplied by the target value y i . The last layer of the network is the linear output layer, which uses the linear function as the transfer function, as shown in Equation ( 7)…”
Section: Neural Network Aided Original Adjustment Methodsmentioning
confidence: 99%
“…Research by Jiang et al. 6 demonstrated that the same chromaticity could be obtained using varied dot area coverages on different substrates, and the printing color could be determined by the synergy of the ink diffusion on the surface of the substrate and the light reflection of the ink itself. Maryam 7 pointed out that the characteristics of the substrate would affect the color presenting of printing.…”
mentioning
confidence: 99%
See 1 more Smart Citation